Manajemen Program Kursus Perhotelan di Lembaga Kursus dan Pelatihan Surabaya Hotel School - Reivera, Kevin; Rosyanafi, Rofik Jalal (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
The purpose of this study is to describe the management of a hospitality course program which includes planning, organizing, implementing, monitoring, and evaluating. The research method used is descriptive qualitative. Data collection techniques used were interviews, observation, and documentation, with data analysis techniques used were data collection, data reduction, data presentation, and drawing conclusions. The results obtained from this study began with planning which included identifying needs, planning curriculum, planning instructors, planning financing, planning facilities and infrastructure. Organizing programs that cover several aspects of indicator, namely the formation of implementing organizations and the division of tasks by forming an organizational structure and also the division of tasks with their respective competencies. Implementation by opening with greetings and introductions to students, thenian continued with the delivery of learning material interactively, the delivery of learning material was carried out using the question and answer lecture method, and practice then at the end of the learning section was carried out with the presentation/presentation of the results of practice and continued with closing greetings. supervision includes: the level of discipline of the instructor/tutor and students, the ability of the instructor/tutor in learning, the preparation of managers in preparing all program needs. The learning evaluation process is carried out by conducting tests on students at the end of the learning period in accordance with the program taken by students. The evaluation process is also carried out by assessing the performance of the instructor/tutor at the end of the lesson.